A task-sharing intervention for prepartum common mental disorders: Feasibility, acceptability and responses in a South African sample - Maxine Spedding; Dan J. Stein; Tracey Naledi; Bronwyn Myers; Pim Cuijpers; Katherine Sorsdahl (AOSIS, 2020)
Background: Peripartum common mental disorders (CMD) are highly prevalent in low- and middle-income countries (LMIC) such as South Africa. With limited public mental health resources, task sharing approaches to treatment are showing promise. However, little is known about the feasibility and acceptability of, as well as responses associated with problem-solving therapy (PST) for the treatment of prepartum CMD symptoms in South African public health settings. Aim: To investigate participants' preliminary responses to a task sharing PST intervention, and to evaluate the feasibility and acceptability of the intervention. Setting: A Midwife and Obstetrics Unit attached to a Community Health Centre in a Western Cape district. Methods: Using mixed methods, 38 participants' responses to a PST intervention, and their perceptions of its feasibility and acceptability, were explored. Primary outcomes included psychological distress (Self Reporting Questionnaire; SRQ-20) and depression symptoms (Edinborough Postnatal Depression Scale; EPDS). Semi-structured interviews were conducted three after the last session. Six stakeholders were also interviewed. Results: Significant reductions were seen on EPDS (Cohen's d = 0.61; Hedges g = 0.60) and SRQ-20 (Cohen's d = 0.68; Hedges g = 0.67) scores. The intervention's acceptability lay in the opportunity for confidential disclosure of problems; and in relieving staff of the burden of managing of patients' distress. Barriers included lack of transport and work commitments. Conclusion: Results support task sharing PST to Registered Counsellors to treat antenatal CMDs in perinatal primary health care settings. Research is needed on how such programmes might be integrated into public health settings, incorporating other non-specialists.